Optimization of Sandblasting Project Scheduling at PT. Prima Saka Engineering Using the Hungarian Algorithm - Jihan Tria Marena Marena; Nia Nurfitria (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study employs the Hungarian Algorithm to optimize the sandblasting project scheduling at PT. Prima Saka Engineering. Five workers (P1-P5) with different specializations were assigned five tasks: surface preparation (T1), exterior sandblasting (T2), interior sandblasting (T3), primer application (T4), and final quality inspection (T5). The goal was to reduce overall completion time, with each worker being assigned to only one task. The methodical steps comprised matrix building, reduction, and optimality testing. The Hungarian Algorithm generated an optimal assignment with a minimal total time of 1,128 hours, saving 222 hours (16.4%) compared to the previous 1,350-hour method. This study demonstrates that the Hungarian Algorithm provides a mathematically optimal and practically applicable framework for strategic resource allocation and project management.